Proceedings of the 2017 CHI Conference on Human Factors in Computing Systems 2017
DOI: 10.1145/3025453.3025594
|View full text |Cite
|
Sign up to set email alerts
|

CoReach

Abstract: Multi-touch wall-sized displays afford collaborative exploration of large datasets and re-organization of digital content. However, standard touch interactions, such as dragging to move content, do not scale well to large surfaces and were not designed to support collaboration, such as passing an object around. This paper introduces CoReach, a set of collaborative gestures that combine input from multiple users in order to manipulate content, facilitate data exchange and support communication. We conducted an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…et al [31] compared various collaboration strategies on a wallsized display. They also showed that cooperative interaction improves close and loose collaboration [32].…”
Section: Wall-sized Displaysmentioning
confidence: 98%
“…et al [31] compared various collaboration strategies on a wallsized display. They also showed that cooperative interaction improves close and loose collaboration [32].…”
Section: Wall-sized Displaysmentioning
confidence: 98%
“…Albeit not our focus, the size of the display creates the opportunity to let multiple users interact simultaneously. Liu et al [LCBL17] developed collaborative touch gestures for wall displays to support users working together but on different parts of the display. Von Zadow et al [vZRB * 16] created a low-cost system for user tracking called YouTouch!…”
Section: Interacting With Wall Displaysmentioning
confidence: 99%
“…To take this further, interaction through complementary tools should enable users to help each other instead of competing. Phases of close and loose collaboration among users could be supported through territoriality [SCI04] using separate areas on the large screen as suggested by Liu et al [LCBL17] or mobile devices. While our visualization and interaction with SPLOMs already allows multiple focus areas (see Figure 5), for supporting multiple users we would have to add user identification by e.g.…”
Section: Limitationsmentioning
confidence: 99%
“…Multi-user interaction in a collocated scenario is a well-studied topic within computer-supported collaborative work (CSCW). It has been extensively explored on varying form-factors including tabletops [19] and large wall displays [21,30,66]. With the varied and abundant availability of display surfaces, researchers have explored multi-surface and cross-device interactions, for interactions across tabletops, walls, and handheld displays [6,33].…”
Section: Collocated Interactionmentioning
confidence: 99%
“…Sharing one device mitigates problems such as trust and coordination [14], but more importantly, lacks in providing a simultaneous shared and personal space for sensemaking collaboration [16]. Such division of display resources has been shown to facilitate fluid content sharing in multi-user settings [58], as demonstrated with larger tabletop [19,37] and wall displays [30]. It is unclear how such distribution of display space facilitates content sharing and group effort on a foldable, personal device.…”
Section: Introductionmentioning
confidence: 99%